PERKEMBANGAN DAN PROSPEK PERAKITAN PADI TIPE BARU DI INDONESIA - Abdullah, Buang; Tjokrowidjojo, Soewito; Sularjo, Sularjo (Jurnal Penelitian dan Pengembangan Pertanian, 2008)
Development and prospect of new plant type of rice in IndonesiaNew plant type of rice (NPT) has higher yield potential than that of existing high-yielding varieties. Therefore, it is urgent to develop rice varieties having high yield potential to increase rice yield and production. Development of NPT in Indonesia has been started in 1995. Four NPT varieties were released, namely Cimelati (2001) , Gilirang (2002) , Ciapus (2003) , and Fatmawati (2003) . However, those varieties still have disadvantages, such as few tillers and high sterility, and consequently their yield potential are not as high as proposed. NPT which is suitable to Indonesia as a tropical country and pest and disease are still major problem, should have short and sturdy stems(80-100 cm), 12â18 tillers, 150â250 grains/panicle, 85â95% filled grain, weight of 1,000 grains 25-26 g, early maturity (110â120 days) , erect, thick, dark green and have V form leaves, 2-3 leaves stay-green at filing grain stage, long-deep root system, resistant to major pests and diseases, slender grains, and good grain and cooking quality. NPT having those characters could yield 9â13 t/ha and more stable in productivity. In 2001, the NPT development has being intensified by utilizing various gene sources from indica, japonica, and wild species of rice. A number of advanced lines have been produced having better characters than that of NPT varieties released such as better grain filling and resistance against major insects and diseases. Since 2004, recurrent selection and anther culture methods have been implemented to harness NPT development. Elit lines having high yield potential have been produced by using these methods.Keywords: Rice, selection, yield, anther culture, double haploid